PROFESSIONAL DEVELOPMENT OF MATHEMATICS TEACHERS - Vyacheslav I. Efanov; Anna L. Magazinnikova; Nina N. Nesmelova (Высшее образование в России, 2016)
The article presents the experience of course realization for professional development of Mathematics teachers organized in Tomsk State University of Control Systems and Radioelectronics (TUSUR). The authors observe some changes in requirements for Mathematics teaching in accordance with Federal State Educational Standards for higher professional education. They cover the content of Mathematics and the succession of its learning in connection with professional and special subjects. The Faculty of Professional Development of TUSUR has carried out significant work on adaptation of Mathematics teachers to new conditions of their professional activity. The course ‘Professional Competence Development of Mathematics Teachers in accordance with TUSUR Educational Programs’ has been realized and contains some new approaches to professional development process.